2021
DOI: 10.1002/mc.23310
|View full text |Cite
|
Sign up to set email alerts
|

miR‐506‐loaded gelatin nanospheres target PENK and inactivate the ERK/Fos signaling pathway to suppress triple‐negative breast cancer aggressiveness

Abstract: Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer. Some microRNAs (miRNAs) were abnormally expressed in TNBC, and they are closely related to the occurrence and progression of TNBC. Here, we found that miR-506 was significantly downregulated in TNBC and relatively lower miR-506 expression predicted a poorer prognosis. Moreover, we found that miR-506 could inhibit MDA-MB-231 cell viability, colony formation, migration, and invasion, and suppress the ERK/Fos oncogenic signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In addition, FBLN1 was shown to be elevated in normal FB when compared to CAF [58]. High expression of PENK is associated with improved outcomes in GIST patients and is postulated to act as a tumor suppressor [42], inhibit breast tumor growth [41], and is required, in part, for induction of apoptosis through the NF-κB/p53 pathway [59]. Thus, it is plausible that SLIT3, FBLN1, and PENK cooperate and induce apoptosis through different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FBLN1 was shown to be elevated in normal FB when compared to CAF [58]. High expression of PENK is associated with improved outcomes in GIST patients and is postulated to act as a tumor suppressor [42], inhibit breast tumor growth [41], and is required, in part, for induction of apoptosis through the NF-κB/p53 pathway [59]. Thus, it is plausible that SLIT3, FBLN1, and PENK cooperate and induce apoptosis through different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the PENK ligand in the context of growth suppression in breast cancer is minimal and very recent [41], but there is evidence that high expression of PENK is associated with favorable outcomes in patients with gastrointestinal stromal tumors [42].…”
mentioning
confidence: 99%
“…In our previous study, GNs were used to deliver miR-506 for the treatment of triple-negative breast cancer. 31 GNs were negatively charged and could bind with positively charged complex miR-4458-Lipofectamine 2000, as verified by the results of zeta potential analysis. miR-4458 could realize controlled release in 21 d with the aid of GNs (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…The preparation of GNs was similar to the previous study. 31 Briefly, 100 ml acetone solution was added to the same volume of 5% w/v high molecular weight type B gelatin solution, the gelatin was precipitated and dissolved in water at 50 °C, then adjusted to pH 2.5. 2 ml min −1 acetone solution was added to gelatin solution continuously at 1000 rpm to form GNs.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies on gelatin-based sustained- and controlled-release delivery systems for miRNA therapeutics. Liu et al [ 106 ] demonstrated for the first time that a gelatin-based nanosphere delivery system incorporating miR-506 mimic led to a marked inhibition of tumor growth and metastasis in TNBC xenograft models in mice.…”
Section: Nanocarrier Systems To Deliver Mirna-based Therapeuticsmentioning
confidence: 99%